Application of the Jigsaw Type Cooperative Learning Model in Increasing Interest in Learning at SMPN 19 Palu - Sukmawati, Sukmawati; Jamaludin, Jamaludin; Alanur, Shofia Nurun; Saskia, Saskia; Japar, Desianti; Salsabila, Zelika; Setiawati, Lilis; Santika, Santika; Jannah, Siti Zahrotul; Amir, Hapsa (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
The Jigsaw type cooperative learning model is an effective approach in increasing students' interest in learning, especially at SMPN 19 Palu. This research aims to explore how the application of the Jigsaw model can influence student motivation and learning outcomes. In this model, students are divided into small groups, where each group member is responsible for learning a certain part of the lesson material and then teaching it back to other group members. The research results show that the application of the Jigsaw model can significantly increase students' interest in learning. Students involved in cooperative learning show an increase in activeness and participation during the teaching and learning process. In addition, this model also helps students to develop social and communication skills, which are very important in the modern educational context. With more intensive interaction between students, they become more motivated to learn and more confident in expressing their opinions. This research also notes that students who learn with the Jigsaw model tend to have a better understanding of the subject matter.